Target Zero (An Agent Zero Spy Thriller-Book #2) - Jack, Mars (Lukeman Literary, 2019)
"One of the best thrillers I have read this year." --Books and Movie Reviews (re Any Means Necessary) In this follow up to book #1 (AGENT ZERO) in the Kent Steele spy series, TARGET ZERO (Book #2) takes us on another wild, action-packed ride across Europe as elite CIA agent Kent Steele is summoned to stop a biological weapon before it devastates the world-all while grappling with his own memory loss. Life returns only fleetingly back to normal for Kent before he finds himself summoned by the CIA to hunt down terrorists and stop another international crisis-this one even more potentially devastating than the last. Yet with an assassin hunting him down, a conspiracy within, moles all around him and with a lover he can barely trust, Kent is setup to fail. His memory is quickly returning, though, and with it, flashes into the secrets of who he was, what he'd discovered, and why they are after him. His own identity, he realizes, may be the most perilous secret of all. TARGET ZERO is an espionage thriller that will keep you turning pages late into the night. "Thriller writing at its best." --Midwest Book Review (re Any Means Necessary) Also available is Jack Mars' #1 bestselling LUKE STONE THRILLER series (7 books), which begins with Any Means Necessary (Book #1), a free download with over 800 five star reviews!
Keywords: Dobrodružství, napětí, thrillery